Kostogris S.G., Misliborski V.V. Methods of controlled influence on elastic plastic characteristics of a nominal-ly stationary frictional contact. - Костогриз, С. Г.; Мисліборський, В. В. (Problems of Tribology, 2018)
The system of engineering methods of directed influence on elastic-plastic and visco-elastic characteristics of NNFK is substantiated. Allowed levels of realization of this influence and, in particular: calculation and design of nominally fixed joints of machine-building constructions; technology of processing and assembly of connection elements; operation of machine-building constructions. Mechanism of influence on tangential stiffness of NNFK is developed. The analytical dependence for calculating the required tension in the connection, at which the necessary value of the tangential stiffness of the contact is provided, is established. It is shown that the arithmetic mean height of the irregularities of the contact surfaces has a significant influence on the tangential stiffness of the contact and an analytical dependence is obtained for its determination on the condition of providing a given level of tangential stiffness of the contact. The given recommendations for application of technological methods of treatment of contact surfaces that would have an impact on the tangential stiffness of the contact. The formula of the tangential stiffness of the contact in the structure of the torsional rigidity of the "shaft-sleeve" connections and the elements of the shaft conduits is derived. It is shown that the average tangential stiffness of the NNFK can be altered by increasing or decreasing within the limits of the plasticity parameter. An increase in the contact's plasticity parameter from 0 to 4 allows a 6.8-fold reduction in the average tangential stiffness in the elastic-plastic deformation zone and 2.4 times in the elastic deformation zone. Effective method of influencing the plastic properties of the NNFK is the change in certain limits of the coefficient of clutch in contact due to the creation of a tension in it, which provides the corresponding value of the coefficient of clutch, and thus the parameter of plasticity of the contact. Two approaches are proposed for influence on creep in NNFK - the first of them is based on the dependence of relative deformation in contact with creep from the coefficient of clutch reserve in contact, and the second - on providing such value of this coefficient, in which the relative deformation is at an acceptable level. It is shown that the creep can be influenced by cycling the discharge and loading of the contact at intervals of time when the creep deformation reaches a level close to or equal to the permissible value. Formulas for calculating these time intervals are derived.